Carbon nanotube composite film as well as preparation method and application thereof

Through electrophoretic deposition and intermolecular surface tension in the filling resin, the problem of uneven distribution of carbon nanotubes in carbon nanotube composite film is solved, and the preparation of carbon nanotube composite film with high sensitivity, rapid response and good flexibility is achieved.

CN119798732AInactive Publication Date: 2025-04-11GUANGZHOU UNIVERSITY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411860765.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The method of preparing carbon nanotube composite films in the prior art is costly and complex in the process. In the electrophoretic deposition method, carbon nanotubes are prone to form aggregates, resulting in uneven distribution and poor sensitivity and stability.

Method used

Carbon nanotubes are deposited on the copper sheet by electrophoresis, and the resin is wet and filled between the copper sheets with the surface tension between molecules, controlling the spacing of the copper sheets to ensure the uniform distribution of the carbon nanotubes.

Benefits of technology

The uniform distribution of carbon nanotube layers in the carbon nanotube composite film is achieved. The obtained film has excellent sensitivity, fast response speed, high stability, and good flexibility and strength, which is suitable for the preparation of sensors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798732A_ABST
    Figure CN119798732A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon nano tube composite film as well as a preparation method and application thereof, and relates to the technical field of carbon nano composite materials. The preparation method comprises the following steps: by taking a copper sheet as a cathode and a carbon nanotube dispersion liquid as an electrolyte, arranging an anode, carrying out electrophoretic deposition, and depositing the carbon nanotubes on the surface of the copper sheet; taking two copper sheets with the same deposition time, enabling the surfaces, containing the carbon nanotubes, of the two copper sheets to be opposite, and fixing the copper sheets to enable the distance between the two copper sheets to be 0.01-0.04 mm; resin is applied to the edges of the fixed copper sheets, and the space between the two copper sheets is infiltrated and filled with the resin through intermolecular surface tension; and curing the resin filled between the copper sheets, and separating the copper sheets to obtain the carbon nanotube composite film. The obtained film has the advantages of excellent sensitivity, fast response speed, high stability and good flexibility, and is suitable for preparing sensors, especially flexible sensors or pressure-sensitive sensors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of carbon nanocomposite materials, and in particular to a carbon nanotube composite film and a preparation method and application thereof. Background Art

[0002] With the continuous advancement of medical technology, wearable devices have become an important tool for monitoring health status, preventing diseases, and promoting lifestyle improvements. Among these devices, sensors are the core components, and their performance directly determines the accuracy of wearable devices in monitoring physiological indicators. Sensors are divided into two categories: flexible sensors and rigid sensors. Flexible sensors are favored because they can better fit the contours of the human body and provide better signal transmission.

[0003] In flexible sensors, the selection of conductive fillers has a decisive influence on the performance of the sensor. At present, the main conductive fillers are divided into two categories, carbon-based conductive fillers and metal nano-conductive fillers. Among them, carbon nanotubes (CNTs) have attracted widespread attention due to their low Young's modulus, light weight, corrosion resistance and other characteristics. The carbon nanotube film derived from it as a conductive filler is lightweight and cost-effective. It also shows excellent corrosion resistance, temperature stability and adjustable conductivity, and has excellent flexibility and elasticity. These characteristics make carbon nanotube films have significant advantages in the field of flexible sensors. Therefore, the development of carbon nanotube film technology is of great significance to promoting the development of wearable device technology.

[0004] The existing methods for preparing carbon nanotube composite film are mainly divided into the following categories: (1) solution spin coating: by coating liquid material on a high-speed rotating substrate, centrifugal force is used to evenly spread the liquid to form a film; (2) chemical vapor deposition: a solid film is deposited on the surface of a substrate through a chemical reaction in the gas or vapor phase; (3) vacuum filtration membrane method: a composite film is prepared using a vacuum pressure difference. However, these preparation methods are expensive and have complex production processes. Compared with these preparation methods, the electrophoretic deposition method disclosed in the prior art is a relatively simple process for preparing thin films. It is a technology that uses an electric field to drive charged particles to migrate in a suspension and deposit on the electrode surface to form a thin film. However, due to their strong van der Waals forces, carbon nanotubes are more likely to form aggregates in the electrophoretic deposition method, which makes their dispersion in the medium somewhat difficult. At the same time, the preparation of carbon nanotube films by electrophoretic deposition generally requires the deposited carbon nanotubes to be filled and infiltrated with resin to form a film. Currently, commonly used methods include mechanical stirring, etc. The mechanical forces of these methods can easily destroy the distribution of the deposited carbon nanotubes, resulting in uneven distribution of carbon nanotubes in the obtained carbon nanotube films, and poor sensitivity and stability. Summary of the invention

[0005] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, the purpose of the present invention is to provide a method for preparing a carbon nanotube composite film, and to combine the surface tension between molecules to adsorb the resin onto the copper sheet on which the carbon nanotubes are deposited, so as to ensure that the carbon nanotubes are evenly distributed in the formed carbon nanotube composite film.

[0006] A second aspect of the present invention is to provide a carbon nanotube composite film.

[0007] A third aspect of the present invention is to provide a sensor.

[0008] In order to achieve the above object, the technical solution adopted by the present invention is:

[0009] A first aspect of the present invention provides a method for preparing a carbon nanotube composite film, comprising the following steps:

[0010] Using a copper sheet as a cathode, using a carbon nanotube dispersion as an electrolyte, setting an anode, and performing electrophoretic deposition to deposit the carbon nanotubes on the surface of the copper sheet;

[0011] Take two copper sheets with the same deposition time, place the sides containing carbon nanotubes opposite to each other, and fix the copper sheets so that the distance between the two copper sheets is 0.01 to 0.04 mm;

[0012] Applying resin to the edge of the fixed copper sheet, and using the intermolecular surface tension to make the resin infiltrate and fill between the two copper sheets;

[0013] The resin filled between the copper sheets is cured, and the copper sheets are separated to obtain a carbon nanotube composite film.

[0014] The present invention deposits carbon nanotubes on copper sheets by electrophoretic deposition, controls the spacing between the copper sheets, and utilizes the surface tension between molecules to infiltrate the filling resin. Carbon nanotubes are nano-scale materials with small diameters. The contact area between the liquid resin and the carbon nanotube wall is relatively large. The surface tension and adhesion of the carbon nanotubes are significant, and the resin can be fully expanded to fully penetrate the carbon nanotube deposition surface.

[0015] In the preparation method of the present invention, the spacing between the copper sheets is controlled, and the spacing between the copper sheets is extremely small. When the liquid epoxy resin glue is dripped on the edge of the copper sheet, the resin tends to adhere to the surface of the copper sheet due to the surface tension when the resin contacts the carbon nanotubes, so that the epoxy resin glue is completely infiltrated and filled between the copper sheets. Compared with the traditional mechanical stirring method for preparing carbon nanotube composite films, the attraction between the molecules will not destroy the distribution shape of the carbon nanotubes, and the integrity of the carbon nanotubes is extremely well guaranteed. At the same time, by controlling the spacing between the copper sheets, it can ensure that the resin is fully infiltrated and filled, and the flow rate is not too fast to destroy the distribution of the carbon nanotubes, or defects such as cavities and bubbles appear. Therefore, the preparation method of the present invention realizes the uniform distribution of the carbon nanotube layer in the carbon nanotube composite film, and the obtained carbon nanotube composite film has high sensitivity and stability, and has good flexibility and strength. Compared with other preparation methods, the preparation method of the present invention has a simple process, low preparation cost, and is suitable for mass production.

[0016] In some embodiments of the present invention, the distance between the two copper sheets is 0.015-0.03 mm.

[0017] In some embodiments of the present invention, the distance between the two copper sheets is 0.015-0.025 mm.

[0018] In some embodiments of the present invention, the electrophoretic deposition time is 0.6 to 4 minutes.

[0019] In some embodiments of the present invention, the electrophoretic deposition time is 1 to 4 minutes.

[0020] In some specific embodiments of the present invention, the electrophoretic deposition time is 2 to 3 minutes.

[0021] Limiting the electrophoretic deposition time is beneficial to improving the uniformity of carbon nanotube distribution and the sensitivity of the prepared carbon nanotube film.

[0022] In some embodiments of the present invention, the carbon nanotubes are carboxylated carbon nanotubes.

[0023] In some embodiments of the present invention, the diameter of the carbon nanotube is 5 to 20 nm.

[0024] In some embodiments of the present invention, the carbon nanotube dispersion is a carbon nanotube anhydrous ethanol dispersion.

[0025] In some embodiments of the present invention, the carbon nanotube dispersion contains a soluble metal salt.

[0026] In some embodiments of the present invention, the soluble metal salt comprises a nitrate, such as aluminum nitrate.

[0027] Soluble metal salts are added to the carbon nanotube dispersion and dissolved in anhydrous ethanol to provide cations. Carboxylated carbon nanotubes are further used. The surface of the carboxylated carbon nanotubes can adsorb cations, so that the carbon nanotubes move toward the cathode under the action of the electric field and are evenly deposited on the surface of the copper sheet.

[0028] In some embodiments of the present invention, the resin includes epoxy resin; the viscosity of the epoxy resin at 25° C. is 250 to 450 mPa·s.

[0029] In some embodiments of the present invention, the viscosity of the epoxy resin at 25° C. is 300-400 mPa·s.

[0030] Controlling the viscosity of the epoxy resin is beneficial for controlling the flow rate of the epoxy resin during the infiltration and filling process.

[0031] In some embodiments of the present invention, the resin is obtained by mixing epoxy resin A glue and B glue; the volume ratio of the A glue to the B glue is (1.5-2.5):1.

[0032] In some embodiments of the present invention, the viscosity of the gel A at 25° C. is 600-800 mPa·s.

[0033] In some embodiments of the present invention, the viscosity of the B glue at 25° C. is 50 to 80 mPa·s.

[0034] In some embodiments of the present invention, the material of the anode includes graphite or stainless steel.

[0035] The second aspect of the present invention provides a carbon nanotube composite film prepared by the preparation method described in the first aspect of the present invention.

[0036] In some embodiments of the present invention, the carbon nanotube composite film includes an intermediate layer and a surface layer; the surface layers are located on both sides of the intermediate layer; the intermediate layer is a resin layer, and the surface layers are a composite layer of carbon nanotubes and resin.

[0037] In some embodiments of the present invention, in the carbon nanotube composite film, the mass content of the carbon nanotubes is 0.1-1%.

[0038] The third aspect of the present invention provides a sensor, which includes the carbon nanotube composite film prepared by the preparation method described in the first aspect of the present invention, or the carbon nanotube composite film described in the second aspect of the present invention.

[0039] In some embodiments of the present invention, the sensor comprises a flexible sensor or a pressure-sensitive sensor.

[0040] In some embodiments of the present invention, the sensor comprises a flexible pressure-sensitive sensor.

[0041] Compared with the prior art, the present invention has the following beneficial effects:

[0042] The preparation method of the present invention deposits carbon nanotubes on copper sheets by electrophoretic deposition, and then utilizes the surface tension between molecules to make the resin infiltrate and fill between the copper sheets, while controlling conditions such as the distance between the copper sheets to ensure that the obtained carbon nanotube composite film has a good three-layer structure and avoids defects such as voids, bubbles, and uneven distribution of carbon nanotubes. The obtained carbon nanotube composite film has excellent sensitivity, fast response speed, high stability, and good flexibility and strength, and is suitable for preparing sensors, especially flexible sensors or pressure-sensitive sensors. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 This is a flow chart of preparing a carbon nanotube composite film in an embodiment of the present invention.

[0044] Figure 2 This is a SEM image of the carbon nanotube composite film prepared in Example 1 of the present invention; wherein, Figure 2 b is Figure 2 A partial enlarged view of a.

[0045] Figure 3 This is a SEM image of the carbon nanotube composite film prepared in Example 5 of the present invention; wherein, Figure 2 b is Figure 2 A partial enlarged view of a.

[0046] Figure 4 This is a comparison chart of the response speeds of the carbon nanotube composite films prepared in Examples 1 to 5 of the present invention.

[0047] Figure 5 This is a physical picture of the carbon nanotube composite film prepared in Example 1 of the present invention; wherein, Figure 5 a. Figure 5 b shows the flattened graph and the bent graph respectively.

[0048] Figure 6 The SEM images of the cross sections of the carbon nanotube composite films prepared in Example 1 and Comparative Examples 1-2 of the present invention; wherein: Figure 6 a. Figure 6 b and Figure 6 c represents the SEM images of the thin film cross sections of Example 1, Comparative Example 1 and Comparative Example 2 respectively.

[0049] Figure 7 This is a physical picture of the carbon nanotube composite film prepared in Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0050] The present invention is further described in detail below by specific examples. Unless otherwise specified, the raw materials, reagents or devices used in the examples and comparative examples can be obtained from conventional commercial sources or can be obtained by prior art methods. Unless otherwise specified, the experiments or test methods are conventional methods in the art.

[0051] The preparation process of the carbon nanotube composite film in the following embodiments of the present invention is as follows: Figure 1 shown.

[0052] The diameters of the carbon nanotubes used in the embodiments and comparative examples are all in the range of 5 to 20 nm. Detailed descriptions are given below in conjunction with different embodiments and comparative examples.

[0053] Example 1

[0054] A method for preparing a carbon nanotube composite film comprises the following steps:

[0055] A square copper sheet with a side length of 15 mm and a thickness of 1 mm was selected, ultrasonically cleaned and vibrated with deionized water for multiple times, and the surface was polished several times with sandpaper to remove dust and impurities on the surface;

[0056] A 0.01 mg / mL carboxylated multi-walled carbon nanotube anhydrous ethanol dispersion was prepared, and 0.01 g aluminum nitrate was added thereto. After mixing, the mixture was ultrasonically treated in an ultrasonic cleaning machine for 30 minutes to obtain a uniformly dispersed carbon nanotube anhydrous ethanol suspension;

[0057] Connect the stainless steel plate to the positive pole of the DC regulated power supply as the anode, and connect the copper sheet to the negative pole of the DC power supply as the cathode; place the electrodes in the prepared carbon nanotube anhydrous ethanol suspension, with an electrode spacing of 1 cm, connect the power supply, and perform electrophoretic deposition for 3 minutes; deposit two copper sheets under the same conditions; and dry after deposition;

[0058] The two copper sheets with carbon nanotubes distributed on their surfaces are placed opposite to each other, with the opposite surface being the surface containing carbon nanotubes, and two feeler gauges with a thickness of 0.02 mm are placed between the copper sheets, and the distance between the copper sheets is controlled to be 0.02 mm, with the feeler gauges positioned at the edges of the copper sheets, and then the two copper sheets are fixed using an acrylic frame; epoxy resin AB glue is prepared in a volume ratio of 2:1, the viscosity of A glue is 600-800 mPa·s (25°C), the viscosity of B glue is 50-80 mPa·s (25°C), and the viscosity of the epoxy resin after mixing is 300-400 mPa·s (25°C), and the AB glue is stirred and mixed evenly and left to stand for 5-7 minutes until the bubbles dissipate;

[0059] Drop epoxy resin glue on the edge of the copper sheet, use the intermolecular surface tension to absorb the epoxy resin, and after the epoxy resin is fully infiltrated and filled, let the epoxy resin stand and solidify at room temperature, disassemble the copper sheet, and tear off the film to obtain the carbon nanotube composite film.

[0060] Example 2

[0061] A method for preparing a carbon nanotube composite film, which differs from Example 1 in that the electrophoretic deposition time is 30 seconds; the rest is the same as Example 1.

[0062] Example 3

[0063] A method for preparing a carbon nanotube composite film, which differs from Example 1 in that the electrophoretic deposition time is 45 seconds; the rest is the same as Example 1.

[0064] Example 4

[0065] A method for preparing a carbon nanotube composite film, which is different from Example 1 in that the electrophoretic deposition time is 2 minutes; the rest is the same as Example 1.

[0066] Example 5

[0067] A method for preparing a carbon nanotube composite film, which differs from Example 1 in that the electrophoretic deposition time is 5 minutes; the rest is the same as Example 1.

[0068] Comparative Example 1

[0069] A method for preparing a carbon nanotube composite film, which is different from Example 1 in that the thickness of the feeler gauge is 0.05 mm, that is, the distance between the copper sheets is 0.05 mm; the rest is the same as Example 1.

[0070] Comparative Example 2

[0071] A method for preparing a carbon nanotube composite film, which is different from Example 1 in that the thickness of the feeler gauge is 0.1 mm, that is, the distance between the copper sheets is 0.1 mm; the rest is the same as Example 1.

[0072] Comparative Example 3

[0073] A method for preparing a carbon nanotube composite film comprises the following steps:

[0074] 0.01 g of carbon nanotubes were added to 10 mL of alcohol, and then 10 g of epoxy resin was added to obtain a mixed solution, which was then mechanically stirred for 2 minutes, and then subjected to ultrasonic dispersion treatment for 8 minutes; the treated solution was placed in a mold, cured at room temperature, and then disassembled to obtain a carbon nanotube composite film.

[0075] Comparative Example 4

[0076] A method for preparing a carbon nanotube composite film is prepared by using a dissolution and adhesion technique, and the steps are as follows:

[0077] 5.0 g of urea was dissolved in 100 g of deionized water under magnetic stirring to obtain a transparent solution; 0.15 g of carbon nanotubes was mixed for 25 minutes under ultrasonic dispersion to obtain a uniform black carbon nanotube dispersion; the prepared carbon nanotube dispersion was immersed in the transparent solution at a temperature of 90°C, and after 5 seconds, the sample was further washed with deionized water and ethanol for 5 times, then placed on a polytetrafluoroethylene plate, and then dried in a vacuum oven at 40°C for 5 hours, and a carbon nanotube-modified carbon nanotube composite film was obtained using surface micro-dissolution and adhesion technology.

[0078] Comparative Example 5

[0079] A method for preparing a carbon nanotube composite film is prepared by coating technology, and the steps are as follows:

[0080] Glucose powder was added to a PDMS (polydimethylsiloxane) solution, PDMS: glucose = 3:1 (mass ratio); after stirring the mixture for 2 hours, the mixture was treated with a 500 W microwave for 5 minutes to form a PDMS foam; the foam was immersed in deionized water and ultrasonically treated for 30 minutes to remove residual glucose in the foam, and then immersed in a 0.01 g / mL carbon nanotube suspension and suspended for 12 hours to obtain a PDMS foam containing a carbon nanotube coating, which was dried in an oven at 40°C for 3 hours and then assembled with a conductive adhesive to obtain a carbon nanotube composite film.

[0081] Comparative Example 6

[0082] A method for preparing a composite film, using spraying technology, is as follows:

[0083] A mixture of epoxy resin and curing agent is applied to the surface of the lotus leaf. After the epoxy resin is completely hardened, the lotus leaf and the epoxy resin mold are separated; then a PDMS (polydimethylsiloxane) solution is poured into the epoxy resin mold with the lotus leaf surface pattern, and the PDMS penetration is promoted in a vacuum chamber. After curing, the patterned PDMS is peeled off from the mold; a graphene ink composed of a small amount of graphene flakes is sprayed onto the patterned PDMS surface to form a continuous film, and then two patterned graphene / PDMS films are stacked face to face to obtain a graphene / PDMS composite film.

[0084] Comparative Example 7

[0085] A method for preparing a composite film, using a photolithography + dipping method, the steps are as follows:

[0086] An 11 mg / L gold nanowire (AuNWs) solution was deposited into Kimberly-Clark toilet paper by simple dip-coating and drying. The dip-coating process was repeated 10 times, and the AuNWs-impregnated tissue paper was sandwiched between a 500 μm thick blank PDMS (polydimethylsiloxane) sheet and a PDMS sheet with an interdigitated electrode array pattern. The PDMS surface was plasma treated before sandwiching to enable conformal contact and strong adhesion to the tissue paper. Finally, a AuNW / PDMS composite film was obtained.

[0087] Results

[0088] 1. Comparative analysis of different electrophoretic deposition times

[0089] (1) Morphological characterization comparison

[0090] In Examples 1 to 5, different carbon nanotube composite films were prepared under the same conditions using different electrophoretic deposition times. The scanning electron microscope (SEM) characterization results of the carbon nanotube composite films prepared in Examples 1 and 5 are as follows: Figure 2 and Figure 3 As shown. Combined Figure 2 and Figure 3 It can be seen that the carbon nanotube composite films prepared in Example 1 and Example 5 present a good three-layer structure, the middle layer is an epoxy resin layer, and the upper and lower surface layers are carbon nanotube and epoxy resin composite layers. Figure 1 and Figure 2 It was found that the carbon nanotube composite film prepared in Example 1 had a more uniform distribution of carbon nanotubes and no obvious defects on the interface than that in Example 5, while the carbon nanotube composite film obtained in Example 5 underwent a more obvious agglomeration phenomenon, and the agglomeration easily caused the carbon nanotubes in this part to be relatively loose, which was easily carried away by the flowing epoxy resin, forming defects, and the obtained film cross-section contained small hole defects.

[0091] It should be understood that although no specific SEM images are provided for the carbon nanotube composite films in Examples 2 to 4, the preparation process is the same, and the intermolecular surface tension is used to make the epoxy resin infiltrate and fill. Therefore, the carbon nanotube composite films in Examples 2 to 4 also have a three-layer structure, that is, the epoxy resin layer serves as the middle layer, and the carbon nanotube and epoxy resin composite layer serves as the upper and lower layers.

[0092] (2) Response speed comparison

[0093] The pressure-sensitive signal response time of the carbon nanotube composite film refers to the speed at which the film responds when subjected to external pressure or strain. This performance is very important for applications such as pressure-sensitive sensors because it determines the sensor's detection speed and sensitivity to external pressure changes.

[0094] The present invention adopts a step response method to test the pressure-sensitive signal response time of the carbon nanotube composite film prepared in Examples 1 to 5, so as to characterize its response speed. A step response signal is emitted by an excitation experimental device. The excitation experimental platform is mainly composed of a waveform generator, an excitation head, a guide rail trolley, a force sensor and a signal acquisition box. The waveform generator is connected to the excitation head to input sinusoidal forces of different frequencies and amplitudes, thereby pushing the guide rail trolley to extrude the film. The film is connected to the acquisition circuit through conductive tape, and the circuit is connected to the acquisition card. The frequency of the acquisition signal is 10Hz; the carbon nanotube composite films prepared in Examples 1 to 5 (referred to as M4, M1, M2, M3, and M5 in sequence) are experimented in sequence to obtain the pressure signal response time of each carbon nanotube composite film; in order to ensure the accuracy of the response time, the response time 1ms of the force sensor ymc502F01 is added to the measured response time of the carbon nanotube composite film. The results are as follows: Figure 4 As shown in the figure, it can be seen that different electrophoretic deposition times have a significant effect on the response time of the formed carbon nanotube composite film, which may be caused by the different distribution morphologies of carbon nanotubes. The response time of the carbon nanotube composite film (M4) prepared in Example 1 is 14.4ms, which is longer than the response time of the film (M5) prepared in Example 5. Figure 2 and Figure 3 It can be seen from the comparison that the morphology of the carbon nanotube composite film (M4) of Example 1 is better than that of Example 5 (M5), with fewer defects and more uniform distribution of carbon nanotubes. In addition, the response time of the carbon nanotube composite films prepared in Examples 1 to 5 of the present invention does not exceed 22ms. Overall, the response time is short and can be well applied to various real-time monitoring. At the same time, by further adjusting the deposition time to be greater than 40s, the response time can also be controlled to be less than 20ms.

[0095] 2. Flexibility test

[0096] like Figure 5 As shown, the carbon nanotube composite film prepared in Example 1 of the present invention is bent at a bending angle of about 150°, and no breakage occurs, showing good flexibility. It can be seen that the carbon nanotube composite film of the present invention has good flexibility and strength, and is suitable for flexible electronics such as flexible sensors and flexible displays, as well as biomedicine and other fields.

[0097] 3. Comparative analysis of different copper sheet spacing

[0098] In Example 1 and Comparative Examples 1-2, under the same other conditions, the distance between the two copper sheets when infiltrating the epoxy resin was changed, and the scanning electron microscope images of the obtained carbon nanotube composite film are as follows: Figure 6 As shown (the scale bars are 10μm, 10μm, and 20μm, respectively). Figure 6It can be seen that when the spacing between copper sheets increases to 0.05mm, the flow rate of epoxy resin during infiltration is faster, resulting in the dislocation of carbon nanotubes, no longer presenting a good three-layer structure, and uneven distribution of carbon nanotubes; when the spacing is further increased to 0.1mm, the flow rate of epoxy resin is faster, and excessively large gaps may cause the epoxy resin to flow to fill the gaps first and then infiltrate the carbon nanotubes. Obvious voids and bubbles appear in the cross-section of the formed film, and the internal structural defects are obvious, resulting in a decrease in the performance of the carbon nanotube composite film.

[0099] 4. Comparative analysis of different preparation methods

[0100] (1) Morphology comparison

[0101] Comparative Example 3: The actual photo of the carbon nanotube composite film obtained by conventional mechanical stirring is shown in Figure 7 As shown, it can be seen that the carbon nanotubes are unevenly dispersed in the epoxy resin matrix, and there are defects such as bubbles and holes visible to the naked eye, which destroys the integrity of the film and the overall performance of the film is poor.

[0102] (2) Performance comparison

[0103] The performance of the films prepared in Example 1 and Comparative Examples 3 to 7 were compared, specifically comparing sensitivity, response time and stability. The response time was tested in the same way as in Examples 1 to 5, using a step response method.

[0104] Sensitivity: expressed as sensitivity factor (GF), Where ΔR / R is the instantaneous ratio of the relative change in resistance to the current resistance, and F is the change in external force.

[0105] Stability: The same step response method as above was used to continuously test for 10 h, and the response times of the film were recorded.

[0106] The test results are shown in Table 1 below.

[0107] Table 1 Comparison of film properties of Example 1 and Comparative Examples 3 to 7

[0108]

[0109]

[0110] In Table 1, the conductive filler content is the mass content of the conductive filler in the film (the conductive filler in the examples and comparative examples 3 to 5 is carbon nanotubes, the conductive filler in comparative example 6 is graphene, and the conductive filler in comparative example 7 is gold nanowires), which is calculated by the mass difference before and after preparation. For example, the calculation method of the carbon nanotube content in Example 1 is: record the mass change of the two copper sheets before and after electrophoretic deposition, and this change is the mass of the carbon nanotube deposited, and then weigh the mass of the carbon nanotube composite film obtained. The mass ratio of the deposited carbon nanotubes relative to the mass ratio of the carbon nanotube composite film is the mass content of the carbon nanotubes. According to the same method, the mass ratio of carbon nanotubes in the films of Examples 2 to 5 is calculated, and the results are shown in Table 2 below.

[0111] Table 2 Mass content of carbon nanotubes in carbon nanotube composite films of Examples 1 to 5

[0112] Carbon nanotube mass content / % Example 1 0.6 Example 2 0.1~0.15 Example 3 0.4 Example 4 1

[0113] As can be seen from Table 1, compared with Comparative Examples 3 to 7, Example 1 has significantly better comprehensive performance, and has excellent sensitivity, response time and stability when the film contains a smaller amount of carbon nanotubes. Although the sensitivity of Comparative Example 3 is slightly better than that of Example 1, its stability is significantly lower than that of Example 1, which is only 1000 times, while Example 1 is 38 times that of Example 1. Although Comparative Example 7 has better stability than Example 1, its response time is more than 40 times that of Example 1, and its sensitivity is low. It can be seen that the carbon nanotube composite film obtained by the preparation method of the present invention has stronger comprehensive performance.

[0114] In summary, the preparation method of the present invention deposits carbon nanotubes on copper sheets by electrophoretic deposition, and then utilizes the surface tension between molecules to make the resin infiltrate and fill between the copper sheets, while controlling the conditions such as the distance between the copper sheets to ensure that the obtained carbon nanotube composite film has a good three-layer structure, avoiding defects such as voids, bubbles, and uneven distribution of carbon nanotubes. The carbon nanotube composite film prepared by the present invention has excellent sensitivity, fast response speed, high stability, and good flexibility, and is suitable for preparing sensors, especially flexible sensors or pressure-sensitive sensors.

[0115] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a carbon nanotube composite film, characterized in that: The following steps are involved: Using a copper sheet as a cathode, using a carbon nanotube dispersion as an electrolyte, setting an anode, and performing electrophoretic deposition to deposit the carbon nanotubes on the surface of the copper sheet; Take two copper sheets with the same deposition time, place the sides containing carbon nanotubes opposite to each other, and fix the copper sheets so that the distance between the two copper sheets is 0.01 to 0.04 mm; Applying resin to the edge of the fixed copper sheet, and using the intermolecular surface tension to make the resin infiltrate and fill between the two copper sheets; The resin filled between the copper sheets is cured, and the copper sheets are separated to obtain a carbon nanotube composite film.

2. The preparation method according to claim 1, characterized in that: The electrophoretic deposition time is 0.6 to 4 minutes.

3. The preparation method according to claim 1, characterized in that: The carbon nanotubes are carboxylated carbon nanotubes; And / or, the carbon nanotube dispersion is an anhydrous ethanol dispersion of carbon nanotubes; And / or, the carbon nanotube dispersion contains a soluble metal salt.

4. The preparation method according to claim 1, characterized in that: The resin includes epoxy resin; the viscosity of the epoxy resin at 25° C. is 250 to 450 mPa·s.

5. The preparation method according to claim 1 or 4, characterized in that: The resin is obtained by mixing epoxy resin A glue and B glue; the volume ratio of the A glue to the B glue is (1.5-2.5):

1.

6. The preparation method according to claim 5, characterized in that: The viscosity of the A glue at 25° C. is 600-800 mPa·s; And / or, the viscosity of the B glue at 25° C. is 50 to 80 mPa·s.

7. A carbon nanotube composite film prepared by the preparation method according to any one of claims 1 to 6.

8. The carbon nanotube composite film according to claim 7, characterized in that: The carbon nanotube composite film comprises an intermediate layer and a surface layer; the surface layers are located on both sides of the intermediate layer; the intermediate layer is a resin layer, and the surface layers are a composite layer of carbon nanotubes and resin.

9. The carbon nanotube composite film according to claim 7, characterized in that: In the carbon nanotube composite film, the mass content of the carbon nanotubes is 0.1-1%.

10. A sensor, characterized in that: The sensor comprises the carbon nanotube composite film prepared by the preparation method according to any one of claims 1 to 6, or the carbon nanotube composite film according to any one of claims 7 to 9.

Citation Information

Patent Citations

  • Preparation method of carbon-nanotube-enhanced copper-based composite material

    CN107586981A

  • Flexible temperature sensor based on carbon nanotube epoxy resin composite film, and manufacturing method of flexible temperature sensor

    CN109100039A

  • Carbon nano-tube reinforced carbon fiber thermosetting resin-based composite material preparation method

    CN109265915A

  • The fabrication method of carbon nanotube thin film

    KR1020060060144A

  • Energy Harvesting Devices Using Carbon Nanotube (CNT)-Based Electrodes

    US20120043858A1